86 Gliomatosis peritonei associated with ovarian germ cell tumours- a clinicopathological case series. (13th November 2020) - Jayraj, A; Kumar, S; Bhatla, N; Thulkar, S; Thulkar, S; Kumar, L
Abstract : Introduction: Gliomatosis peritonei (GP) is a rare condition characterized by the presence of mature glial tissue in the peritoneum of patients with ovarian teratomas. In this study, we investigated the clinicopathological features of ovarian teratoma with GP. Methods: From 2016 to 2019, cases of ovarian teratoma with GP treated at AIIMS, New Delhi were retrospectively analyzed for pathology, treatment, survival and prognostic information. Results: The median age of five patients identified with GP was 27 years. All patients had unilateral ovarian mass with moderate to massive ascites at presentation. One patient had bilateral pleural effusion. The average tumour size was 20 cm. Preoperative serum CA-125 (median:392 IU/mL, 141–882 IU/mL) and alpha-fetoprotein levels (median:1118 ng/mL, 219–2313 ng/mL) were elevated. Four patients underwent conservative surgery, with complete cytoreduction. One patient had mature cystic teratoma, one had low grade immature teratoma and three had high grade immature teratoma. All patients had stage 1A-1C disease. Intranodal glial tissue was identified in external iliac lymph nodes of one patient. Postoperatively, all immature teratoma patients received BEP chemotherapy. One patient developed growing teratoma syndrome and underwent secondary cytoreduction. At median follow-up of 30 months, all patients were alive without disease. Conclusion: GP is associated with favorable outcomes. Presence of significant ascites or pleural effusion and elevated CA 125 and alpha-fetoprotein levels preoperatively in patients with ovarian teratoma is suggestive of gliomatosis peritonei. It may be associated with mature or immature teratoma of any grade of differentiation. Adequate sampling to rule out immature elements is necessary for a definitive diagnosis of GP.